A newly-developed metal artifact reduction algorithm improves the visibility of oral cavity lesions on 320-MDCT volume scans. Issue 1 (February 2015) - Funama, Yoshinori; Taguchi, Katsuyuki; Utsunomiya, Daisuke; Oda, Seitaro; Hirata, Kenichiro; Yuki, Hideaki; Kidoh, Masafumi; Hatemura, Masahiro; Yamashita, Yasuyuki
Abstract Purpose To investigate whether a newly-developed single-energy metal artifact reduction (SEMAR) algorithm applied to images acquired on a 320-MDCT volume scanner reduces image artifacts from dental metal. Methods We inserted the lower right teeth covered with a dental metal alloy and crown in a skull phantom and performed single-volume scanning on a second-generation 320-MDCT scanner. A 12-mm diameter spherical lesion was placed either close to or far from the dental metal. The tube voltage and current were 120 kVp and 80 or 155 mA, respectively. Images were reconstructed with filtered back projection (FBP) or iterative reconstruction (IR), with or without SEMAR. We calculated the signal-to-artifact ratios (SAR) to quantify the visibility of the lesion. Two radiologists inspected 96 images (48 with lesion and 48 without) for the presence or absence of the lesion using a 5-point ordinal scale (1 = definitely absent to 5 = definitely present). Results On images reconstructed with FPB and IR with SEMAR, streak artifacts from the dental metal were reduced substantially compared to images without SEMAR. At 155 mA with the lesion near the dental metal, the SARs were better on FBP and IR images (FBP: 1.7 and 0.5 with and without SEMAR, respectively; IR: 1.6 and 0.9 with and without SEMAR, respectively). The observer visual scores improved with SEMAR (FBP: 4.2 and 3.2 with and without SEMAR, respectively; IR: 4.2 and 3.0). Conclusion The SEMAR algorithm reduces dental metal artifacts and improves lesion detectability and image quality in patients with oral cavity lesions.